Anti-DFS70 among HIV-positive individuals – A prospective study. Issue 4 (August 2018) - Mahroum, Naim; Perez, Dolores; Shovman, Ora; Watad, Abdulla; Gilburd, Boris; Amital, Howard; Levy, Itzchak; Shoenfeld, Yehuda
Abstract: Anti-DFS70 is an anti-nuclear antibody directed against the DFS70 protein, which is produced in response to several stressful events. Since its discovery, this autoantigen–antibody complex has drawn the attention of many researchers, yet many questions remain unanswered. The DFS70 protein is crucial for HIV integration into the host DNA; however, the relationship between anti-DFS70 and HIV is unknown. A protective role of anti-DFS70 against HIV is possible due to the competition between the HIV integrase and the anti-DFS70 antibody on the same target site on DFS70. The current study aimed to assess the prevalence of anti-DFS70 in HIV-positive individuals seeking for possible interrelation. A total of 100 HIV-positive individuals followed up at the HIV unit at Sheba Medical Center were tested for the detection of anti-DFS70. A total of 92 non-HIV subjects, randomly selected, were tested and compared as controls. Chemiluminescence assay by QUANTA Flash was performed to evaluate the presence of anti-DFS70 antibodies. None of the HIV-positive individuals had a positive test result for anti-DFS70 (0%) compared to 10 out of 92 non-HIV individuals (10.9%). This is the first study addressing the prevalence of anti-DFS70 in HIV-positive patients. The rate of anti-DFS70 positivity was found to be significantly lower in HIV-positive individuals than in non-HIV individuals (p = 0.002). The absence of anti-DFS70 in HIV-positive subjects might imply that individuals who lack these antibodies are more susceptible to HIV infection. Further studies with large populations are needed to confirm this hypothesis.